Prevalence of carpal tunnel syndrome and its associated factors among patients with musculoskeletal complaints: a single-center experience from Eastern Ethiopia - Tewodros Yesuf; Asfaw Borsamo; Hailu Aragie; Yared Asmare (BMC Musculoskeletal Disorders)
Abstract Background Carpal tunnel syndrome (CTS) is a well-known chronic focal mononeuropathy caused by the mechanical distortion of the nerve at the carpal tunnel. It affects approximately 5% of the population worldwide and 12.1% in Africa. However, it has severe pain that causes discomfort and disturbs daily activities, the magnitude and its risk factors are poorly understood in Ethiopia. Objectives This study aimed to assess the prevalence and associated factors of carpal tunnel syndrome among patients with musculoskeletal complaints in Dire Dawa, Eastern Ethiopia. Methodology An institution-based quantitative cross-sectional study was conducted on randomly selected 422 participants at Dilchora Referral Hospital from May–July 2023. The primary data were collected by using structured questionnaires and checklists. The history taking, anthropometric measurements, physical examination, and diagnosis of carpal tunnel syndrome were performed by the orthopedicians. The data were collected by the four BSc midwives under strict supervision. The data carefully checked for the accuracy, completeness, and validity. Next, data were put into Epi-data and then exported to SPSS for analysis. Descriptive statistics, bivariate and multivariable logistic regression analyses were carried out. Result The prevalence of clinically confirmed carpal tunnel syndrome was 10.8% (95% CI: 6.99% to 14.6%). A multivariable analysis revealed that physical inactivity [AOR = 3.32 (95% CI: 1.95–5.52)], diabetes mellitus [AOR = 4.23 (95% CI: 1.47–6.97)], hypertension [AOR = 2.5 (95% CI: 1.70–5.65)], hand ratio < 2.1 [(AOR = 4 (95% CI: 1.80–9.66)], and wrist ratio > 0.72 [AOR = 2.1 (95% CI: 1.11–4.72)] were statistically associated with carpal tunnel syndrome. Conclusion The prevalence of carpal tunnel syndrome among the musculoskeletal complaints is 10.8%. Diabetes mellitus, hypertension, physical inactivity, and a wrist ratio > 0.72 were statistically associated with carpal tunnel syndrome. Doing physical exercise, regulating blood sugar levels, and monitoring blood pressure were recommended.